El engagement en los jefes de créditos y cobranzas del Banco Azteca agencia principal Iquitos, febrero 2021 - Rojas Diaz, Andy Fernando (2022)
The Thesis on Engagement in the heads of credits and collections of Banco Azteca main agency Iquitos, February 2021, aims to determine the level of Engagement in the heads of credits and collections of Banco Azteca main agency Iquitos March 2021, the research is of a level Descriptive and with a non-experimental cross-sectional design, the population is made up of all the heads of credits and collections of the Banco Azteca main office in Iquitos, making a total of 22; In this period, it was determined that the Engagement level is 40.91% at the low level, 36.365 at the average level and 22.73% at the high level. In the absorption dimension we find the highest level of engagement with 36.40%, in the dedication dimension the high level is only 9.10% and in the vigor dimension the high level reaches 18.20%